Exploring the Interplay Between Hadith and Islamic Theology: Foundations, Impacts, and Interpretations - Hafiz Fahad Aziz; Mr. Ghulam Qasim (Journal of Religion and Society, 2025)
The interaction between Hadith and Islamic theology is the main pillar of Islamic intellectual tradition and influences the faith, customs and morality of Muslims across the world. In addition, Hadith, which is formed by words, deeds, and authorizations of the Prophet Muhammad (PBUH) is another secondary yet crucial source of guidance to the Quran. It also gives a detailed exposition of Quranic doctrine, especially such branches as worship, morality, and eschatology, thus enhancing Islamic theology (Ilm al-Kalam). This article will discuss the sources of Hadith and its explanations of the major theological terms such as Tawhid (oneness of God), Prophethood as well as the afterlife (Akhirah) and the practical influence of Hadith on Muslim practices, law (Sharia) and morals. The paper has pointed out the methodologies of the Hadith scholars to authenticate the narrations and the differences between Sunni and Shia interpretations as they indicate the theological and historical differences. The discussion of the contemporary issues on the authenticity, relevance, and contextual application of Hadith is also discussed especially with reference to the contemporary issues like gender equality, human rights, and interfaith dialogue. Historians recommend a moderate view, a combination of the traditional study of Hadith and its critical contemporary interpretation to make it relevant. Finally, the article highlights the irreplaceable role of Hadith in Islamic theology, which connects the divine revelation with the real life, but at the same time, it takes into consideration the changing nature of its interpretation in the globalized world. Keywords: Hadith, Islamic theology, Tawhid, Ilm al-Kalam, Prophethood, Eschatology, Sharia, Sunni-Shia interpretations, Authenticity, Contemporary challenges